The Role of School Principals’ Leadership in Improving Teacher Performance at Proskill Health Vocational School Tualang and YPPI Vocational School Tualang, Siak Regency - Nasa, Herlina; Lestari, Slamet (FKIP - Universitas Riau, 2025)
This study aims to analyze the role of school principal leadership in improving teacher performance in vocational high schools in Tualang District and to identify the supporting and inhibiting factors that shape the effectiveness of principal leadership. The study employs a qualitative descriptive approach with a case study design conducted at SMK Kesehatan Proskill Tualang and SMK YPPI Tualang. Data were collected through in-depth interviews with principals, teachers, and school staff, classroom observations, and document analysis, including Education Report Cards and lesson plans. Data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing and verification based on Miles, Huberman, and Saldaña. The findings reveal that principals who apply transformational and instructional leadership are able to improve the quality of instructional planning, implementation, and evaluation, including the strengthening of numeracy and linkages with the labor market. However, limited academic supervision, inadequate facilities, and weak collaboration among teachers still hinder the optimal improvement of teacher performance.